The best book of FoxPro - Robinson, Celeste. 4 0 16; 5 (Carmel, Ind., USA : Hayden Books, 1990)
A guide to the database management system, explains how to create databases, develop applications, use FoxPro accessories, and trouble shoot the FoxPro system.
Covers FoxPro version 1.02--Cover.;Includes index.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; FoxPro (Computer file); Database management.;FoxPro (Computer program);Database management; 20; 2